Pesticides and Prior Informed Consent - Frederick M. Fishel (EDIS)
PI222, a 6-page illustrated fact sheet by Frederick M. Fishel, describes this international information exchange sponsored by the United Nations to assist countries throughout the world in decisions on whether to allow import of chemicals of concern, such as pesticides. Includes additional sources of information. Published by the UF Department of Agronomy, November 2009.